Burning worlds of cartography: a critical approach to climate cosmograms of the Anthropocene. Issue 2 (28th November 2016) - Schneider, Birgit
Abstract : Climate science today makes use of a variety of red globes to explore and communicate findings. These transform the iconography which informs this image: the idealised, even mythical vision of the blue, vulnerable and perfect marble is impaired by the application of the colours yellow and red. Since only predictions that employ a lot of red seem to exist, spectators are confronted with the message that the future Earth that might turn out as envisaged here is undesirable. Here intuitively powerful narrations of the end of the world may connect. By employing methods of art history and visual analysis, and building on examples from current Intergovernmental Panel on Climate Change reports and future scenario maps, this article explores how burning world images bear – intentionally or not – elements of horror and shock. My question explored here is as follows: should 'burning world' images be understood as a new and powerful cosmology? Abstract : This article analyses contemporary world maps of climate change futures from a visual studies perspective, comparing the red temperature maps with the photograph of the Blue Marble with a special focus on color symbolism. The so called 'burning world' cartographies are understood as a current worldview based on maps and data visualisation. e00027